TEMURID PRINCESS GAUHARSHADBEGIM FAMILY AND HER LIFE DURING THE REIGN OF AMIR TEMUR (Scientific journal of the Fergana State University, 2024)
The article analyses on the basis of historical sources the role of the family of the Temurid princess Gavkharshodbegim in the Temurid state, as well as the life and activities of the princesses during the time of Amir Temur.